2022
DOI: 10.1016/j.jval.2021.09.008
|View full text |Cite
|
Sign up to set email alerts
|

A Cost-Utility Analysis of Remote Pulse-Oximetry Monitoring of Patients With COVID-19

Abstract: Objectives Since 2020, COVID-19 has infected tens of millions and caused hundreds of thousands of fatalities in the United States. Infection waves lead to increased emergency department utilization and critical care admission for patients with respiratory distress. Although many individuals develop symptoms necessitating a ventilator, some patients with COVID-19 can remain at home to mitigate hospital overcrowding. Remote pulse-oximetry (pulse-ox) monitoring of moderately ill patients with COVID-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…We developed a decision-analytic Markov model to estimate the cost-effectiveness of COVID-19 booster vaccination (predominately mRNA vaccines, 3 months after 2 nd dose) in those aged ≥16 years in Australia. Markov models are widely used in economic evaluations of population interventions [20] , [21] , [22] , [23] , [24] , [25] , [26] . In one of our previous studies, we have used a Markov model to evaluate the cost-effectiveness of a booster strategy of Pfizer-BioNTech among older adults in the United States (US) [27] .…”
Section: Methodsmentioning
confidence: 99%
“…We developed a decision-analytic Markov model to estimate the cost-effectiveness of COVID-19 booster vaccination (predominately mRNA vaccines, 3 months after 2 nd dose) in those aged ≥16 years in Australia. Markov models are widely used in economic evaluations of population interventions [20] , [21] , [22] , [23] , [24] , [25] , [26] . In one of our previous studies, we have used a Markov model to evaluate the cost-effectiveness of a booster strategy of Pfizer-BioNTech among older adults in the United States (US) [27] .…”
Section: Methodsmentioning
confidence: 99%
“…A recent decision analytical Markov modelling study evaluated the cost-utility of remote pulse oximetry monitoring over a 3-week time horizon from a US health sector perspective. [70] It found that remote monitoring dominates current standard care, by saving USD $11472 and gaining QALYs of 0.013. Besides, people with access to remote monitoring had 87% fewer hospitalisations and 77% fewer deaths.…”
Section: Comparison With Other Studiesmentioning
confidence: 99%
“…Some studies have demonstrated that remote monitoring programmes may be cost effective. A cost-effectiveness analysis of patients presenting to EDs with moderate-to-severe COVID-19 found that those discharged from ED on a remote oximetry pathway had lower rates of mortality, subsequent ED visits and intensive care admissions in the 3 weeks following presentation than those not on the pathway, amounting to an estimated saving of $11 472 per patient [ 43 ]. Importantly, this analysis was unable to account for the other clinical characteristics of those who did and did not receive the intervention.…”
Section: Cost-effectivenessmentioning
confidence: 99%